Pengaruh Gaya Hidup Terhadap Perilaku Keuangan dengan Teman Sebaya sebagai Variabel Intervening pada Mahasiswa STIE Bina Karya Tebing Tinggi - Kumala Vera Dewi; Siti Nurhalijah; Sri Devi; Manda Irawan (STIE Bina Karya, 2023)
The aim of this research is to analyze gay life and related topics in relation to financial risks. In this research, there were 290 students registered at STIE Bina Karya Kota Tebing Tinggi majoring in Management in the fourth semester. According to Slovin rumors, 75 people responded to the survey. The data which is divided into two groups is referred to as primary data in terms of how the partners are rewarded. SmartPLS 3.0 software is the technology used for data analysis. The research results show that lifestyle has a positive and significant effect on financial behavior and peers have a positive and significant effect on financial behavior.